Pengaruh Transfer Pricing, Profitabilitas, dan Leverage Terhadap Penghindaran Pajak (Studi Empiris Pada Perusahaan Coal Production Yang Terdaftar Di BEI 2019-2023) - Fadilah Amal Ramadhan; Dyah Purnamasari (Owner : Riset dan Jurnal Akuntansi, 2025)
Tax avoidance remains a major challenge for state revenues, especially in sectors that are vulnerable to fiscal manipulation, such as the coal industry. This study aims to examine the partial effect of transfer pricing, profitability, and leverage on tax avoidance in coal companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The study uses a quantitative approach based on secondary data obtained from the company's financial statements on the official IDX website and each company. Through a purposive sampling technique, 10 companies were selected from 34 populations, resulting in 50 observations. Transfer pricing is measured using the TP Related Company Transactions Ratio, profitability with Return on Assets (ROA), and leverage with Debt to Equity Ratio (DER). The analysis was carried out using panel data reggresion. The results show that transfer pricing and profitability have an effect on tax avoidance, while leverage has no statistical effect. This finding indicates that companies tend to utilize transfer pricing schemes more intensively when profitability is high, but debt levels are not always an indicator of tax avoidance behavior. This study contributes by analyzing transfer pricing disclosure in high-risk industries. We recommend companies to be fiscally compliant and implement transfer pricing strategies carefully.. Tax authorities need to improve transfer pricing supervision by considering profitability in risk mapping. Future research is expected to be expanded to other sectors or use a qualitative approach to understand managerial motivations behind tax strategies.